Eosinophilic Granulomatosis With Polyangiitis With Thrombotic Microangiopathy: Is Simultaneous Systemic Lupus Erythematosus Associated With Clinical Manifestations?. Issue 45 (November 2015) - Fukui, Shoichi; Iwamoto, Naoki; Tsuji, Sosuke; Umeda, Masataka; Nishino, Ayako; Nakashima, Yoshikazu; Suzuki, Takahisa; Horai, Yoshiro; Koga, Tomohiro; Kawashiri, Shin-ya; Ichinose, Kunihiro; Hirai, Yasuko; et al.
Abstract : Abstract: Eosinophilic granulomatosis with polyangiitis (EGPA) is one of the antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis, which is characterized by vasculitis of the small to medium-sized vessels. On the contrary, thrombotic microangiopathy (TMA) is a life-threatening condition which can cause ischemic organ injury. Although several case reports have described patients with TMA associated with ANCA-associated vasculitis except for EGPA, there are no previous case reports of EGPA associated with TMA. A 71-year-old Japanese man was diagnosed with EGPA based on his asthma, eosinophilia, lung opacity, refractory sinusitis, and positive myeloperoxidase-ANCA. He was also diagnosed with TMA based on peripheral schizocytes and hemolytic anemia. We performed plasmapheresis and started high-dose corticosteroid therapy; thereafter, he improved promptly. His case also fulfilled the classification criteria of systemic lupus erythematosus (SLE) based on the pleural effusion, renal disorder, anemia, thrombocytopenia, positive antidouble-stranded DNA antibody, and low complement. Elements of SLE were thought to affect his clinical course. We reviewed 11 patients with EGPA or hypereosinophilic syndrome (HES) associated with SLE, including our case. Patients with EGPA or HES associated with SLE had more heart complications than patients with simple EGPA or simple HES did. Patients with EGPA or HES associated with SLE had more pleural effusion than patients with simple SLE did. Clinical manifestations of eosinophilia with SLE or SLE with eosinophilia may differ from simple SLE or simple eosinophilia.